Niemann-Pick disease type-B: a unique case report with compound heterozygosity and complicated lipid management - L. Ordieres-Ortega; F. Galeano-Valle; M. Mallén-Pérez; C. Muñoz-Delgado; J. E. Apaza-Chavez; F. J. Menárguez-Palanca; L. A. Alvarez-Sala Walther; P. Demelo-Rodríguez (BMC, 2020)
Abstract Background Niemann-Pick disease (NPD) is a rare autosomal recessive hereditary disease characterized by deficient activity of acid sphingomyelinase. Case presentation We present a case of NPD type B with a unique compound heterozygosity for SMPD1 (NM_000543.4:c.[84delC];[96G > A]) in which both mutations that induce an early stop codon are located before the second in-frame initiation codon. The clinical presentation of the patient is compatible with NPD type B. She was initially diagnosed of Gaucher Disease, but her altered lipid profile led to a clinical suspicion of NPD. Combined high doses of atorvastatin and ezetimibe were given to treat the severe hypercholesterolemia. Conclusions The pharmacological management of the lipid profile in these patients is important. A unique compound mutation in SMPD1 gene is described.